Parametric analysis on the transient two-phase wellbore model applied to the Yangyi high-temperature geothermal field - Chaofan Chen; Hongwei Zhou; Thomas Nagel; Theo Renaud; Dmitri Naumov; Olaf Kolditz; Haibing Shao (Geothermal Energy)
Abstract Purpose In high-temperature geothermal fields, interpretation of the dynamic two-phase state inside the production wells under different wellhead conditions are important to effectively use the geothermal heat source. Therefore, the corresponding wellbore models must have the capability to simulate transient flow and energy state in geothermal wellbores, as well as advective and conductive heat and mass interactions with surrounding formation. Methods In this study, a transient two-phase wellbore model is developed and implemented in the open source software OpenGeoSys, to simulate both flow and energy state in the wellbore, as well as advective and conductive heat and mass interactions with surrounding formation. The model is first verified against analytical solutions and numerical results from the open-source simulator FloWell. The model is then further validated with well logging data from the Yangyi geothermal field in Tibet, China. Results Based on the simulation results of the parametric analysis, the conductive heat loss of the high-velocity geothermal production well in the Yangyi geothermal field is found to be limited and the influence can be safely neglected after 8 h of discharge. The flash point location in the wellbore moves upwards for 112 m along with the decrease in fluid enthalpy by 200 kJ/kg. In the wellbore shut-in process, the wellhead pressure decreases with decreasing velocity, while the location of the flash point does not change much. After wellbore shut-in, a two-phase state still exists in the closed wellbore, and the temperature profile is dominated by conductive heat exchange with the surrounding formation. Taking into account the impact of the feed zone, the mass flow rate of the ZK203 well in the Yangyi geothermal field increases from 122.87 to 126.26 t/h when the wellhead pressure decreases from 1.26 to 1.18 MPa. Conclusion The open-source two-phase wellbore model developed and implemented in this work provides preliminary insights into the transition and evolution of the two-phase state in high-temperature production wells considering advective and conductive interactions with the surrounding formation.